Vernacular newspaper in early 20th century Iloilo the case of the Makinaugalingon (1913-1946). - Ramos, Vispocious I
This is a study on the history of the Makinaugalingon newspaper in Iloilo from its founding in 1913 to its folding up in 1946., This study seeks to examine the factors that led to the founding of the Makinaugalingon. This focuses on the circumstances undergone by the Makinaugalingon throughout the years of its existence, how it was affected by such and how it responded to various situations. Furthermore, it presents the nature of the Makinaugalingon and its operational procedures. Finally, it determines how the Makinaugalingon affected the lives of the Ilonggos and analyzes the Makinaugalingon's contribution to the press during its years of existence and to the writing of local history. The researcher employed formal and informal interviews as data gathering technique. Published and unpublished sources including theses and souvenir programs were employed to supplement the study. This study of the Makinaugalingon is a descriptive one. As a civic oriented newspaper, the Makinaugalingon served to help society by way of its articles published. It had established a purpose of what a print media can do in the service to society which became the basis of the articles it published. The Makinaugalingon helped the people to keep track of information to help them respond and cope with the situations that might affect them. Second, the Makinaugalingon tried to develop social consciousness among the people so that social and political participation be made possible on a wider scale. On the part of the press, the Makinaugalingon had created many seasoned journalists in Hiligaynon. The Makinaugalingon is an indispensable material both for general information and scholarly research, a useful tool for retrospective information.